Influence of Hydration on the Structure and Interactions of Ethaline Deep‐Eutectic Solvent: A Spectroscopic and Computational Study. Issue 10 (14th April 2020) - Kalhor, Payam; Zheng, Yan‐Zhen; Ashraf, Hamad; Cao, Bobo; Yu, Zhi‐Wu
Abstract: Deep‐eutectic solvents (DESs) are regarded as alternative green solvents to ionic liquids. In this work we report the structural properties and hydrogen bonding (H‐bonding) interactions of an aqueous DES system. The used DES, ethaline (ETH), is composed of choline chloride and ethylene glycol (EG) in 1 : 2 molar ratio. The investigations were carried out by FTIR spectroscopy combined with quantum chemical calculations. Excess spectroscopy and two‐dimensional correlation spectroscopy (2D‐COS) were used to explore the data in detail. The results showed that, upon mixing, ETH transforms to EG dimers and trimers and D2 O clusters transform to various ETH‐D2 O complexes. Theoretical calculations show that water molecules insert between the anion and cation of ETH, break the strong doubly ionic Cl −… H−OCh+ H‐bond, share charges of the ions and form H‐bond with them, thus modulate the interaction properties of ETH. This study deepens our molecular‐level understanding of the system and would shed light on its applications. Abstract : What's in the mix? A combination of infrared, excess infrared and two‐dimensional correlation spectroscopies along with quantum chemical calculations were employed to study the structural and hydrogen bonding properties of a series of pseudo‐binary mixtures containing a deep‐eutectic solvent (ethaline) and water. The results show a transformation from neat ethaline and water to ethylene glycol dimers and trimers and ethaline‐water complexes upon mixing.